Chromatography : basic principles, sample preparations and related methods - Lundanes, Elsa; Reubsaet, Leon; Greibrokk, Tyge (Weinheim, Germany : Wiley-VCH Verlag GmbH & Co. KGaA, 2014)
This is a text on chromatography which is easy to grasp for undergraduates and technicians. The book includes all recent technology advances and has core textbook features further improving the learning experience.
Includes bibliographical references and index.
Keywords: Chromatographic analysis; Chromatographie